Pelaksanaan Metode Ahe dalam Pembelajaran Tambahan Membaca Anak Usia Dini: Studi Kasus Partisipatif Belajar Tambahan Membaca Anak Usia Dini Lembaga Ahe di Unit Purwabakti Bogor - Ai Yulianah; Zaenal Abidin; M Taufiq Aziz (Prodi PGMI IAI Sahid, 2023)
This study aims to find out how the Ahe Method is implemented in additional early childhood reading learning in the Purwabakti unit, Bogor. To achieve this goal, this research was designed using a participatory case study research type, with a research setting in the Purwabakti unit. The research informants are unit owners, supervising teachers and parents. Using audio, video, field notes, and documentation research data types. Data collection techniques by way of observation, interviews, and documents. To test the validity of the data used the technique of triangulation techniques, sources, and time. Data analysis used an interactive analysis model by means of data reduction, data presentation, and drawing conclusions/verifications. The results of this study indicate that: Researchers found that the development of children's reading skills developed well and the Ahe Method was fun and could foster children's enthusiasm and interest in learning. Based on the results of research on the implementation of learning to read Ahe Purwabakti in accordance with the techniques set by the Central Ahe by carrying out 6 learning steps, including the number eight brain exercise, sleep evaluation, reading modules, enrichment, writing and games. As for Ahe Purwabakti, it has its own uniqueness, namely innovating games with the aim that children don't feel bored in learning to read at Ahe Purwabakti. The Central Ahe has games like: wicket game, buying and selling game, chicken game and glance game. Whereas in Ahe Purwabakti there are additional games including: hide and seek game, circular donut game, rock paper scissors game, card clap game and police arrest game.